DNA METHYLATION PATTERN OF ESTROGEN RECEPTOR ALPHA (ERΑ) GENE PROMOTER REGION AND ITS INFLUENCE ON MILK PRODUCTION PERFORMANCE IN XINONG SAANEN DAIRY GOATS - Gaofeng Pei; Pei Gao; Haonan Li; Tao Liang; Feng Wang; Chuanying Pan; Hong Chen; Xianyong Lan (Journal of Animal and Plant Sciences, 2015)
The aim of this study was to identify DNA methylation pattern of estrogen receptor alpha (ERα) gene promoter region and to evaluate its association with milk production performance of Xinong Saanen dairy goats. The results showed that there was no significant difference in DNA methylation percentage (MP) in mammary glands samples collected during dry period and milking period. Interestingly, the methylation of ERαgene was breed-specific, and the high milk yielding breed of Xinong Saanen dairy goats appeared to be linked with hypomethylation of the gene (P<0.001) when compared with other dairy breeds. Methylation share rate (MSR) of Xinong Saanen dairy goats ranged from 0 to 0.105. Furthermore, the DNA MP in whole blood samples was significantly higher than that in mammary gland (P<0.001), suggesting that the methylation of this gene was tissue-specific. For the average milk density (AMD), the DNA methylation level of ERα gene in junior AMD group (JP) was significantly lower than that in senior AMD group (SP) (P<0.05). The MP of CpG-12 and CpG-15 dinucleotide loci of SP group were significantly higher than those of JP group (P<0.05 and P<0.05), respectively. Therefore, the two specific CpG-dinucleotide loci can be considered as epigenetic markers, which may contribute in improving milk production performance through epigenetic marker-assisted selection (eMAS) in dairy goats.
Keywords: Dairy goat; Estrogen receptor alpha (ERα) gene; DNA methylation; Milk production performance; Influence